Visual search for schematic emotional faces: Angry faces are more than crosses - Dickins, D.; Lipp, Ottmar (Taylor and Francis, 2014)
Recent studies of the face in the crowd effect, the faster detection of angry than of happy faces in visual search, suggest that for schematic faces it reflects on perceptual features like inward pointing lines rather than on emotional expressions. Removing a potential confound, Experiments 12 replicate the preferential detection of stimuli with inward pointing lines, but Experiment 2a indicates that a surrounding circle is required for the effect to emerge. Experiments 37 failed to find evidence for faster detection of schematic faces comprising only the elements critical for the faster detection of angry faces according to a low level visual feature account, inward tilted brows and upturned mouth. Faster detection of anger was evident if eyes or eyes and noses were added, but only if their placement was consistent with the first order relations among these elements in a human face. Drawing the critical elements in thicker, higher contrast lines also led to an anger advantage, but this was smaller than that seen for the complete faces. The present results suggest that, while able to support faster target detection, a prevalence of inward pointing lines is not sufficient to explain the detection advantage of angry schematic faces.